2015
DOI: 10.1159/000437336
|View full text |Cite
|
Sign up to set email alerts
|

Lower Urinary Tract Symptoms and Aging: The Impact of Chronic Bladder Ischemia on Overactive Bladder Syndrome

Abstract: Introduction: The overactive bladder syndrome (OAB) is one of the most common and bothersome subsets of lower urinary tract symptoms (LUTS), affecting predominantly the aged population, with a worldwide distribution. This syndrome has not been completely understood, yet the aging process and the decreased blood flow to the bladder have been highlighted as closely related to this phenomenon. Materials and Methods: We performed a search on the online database PubMed/MEDLINE with the following MESH terms: ‘Overac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 68 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…These findings could be attributed to age-related changes in the urinary tract [14,15] and to severe incontinence being more common in older than younger patients with OAB [2,16] . Incontinence is more prevalent in women [17,18] and our population was predominantly female, although 55% of men also presented with wet OAB.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be attributed to age-related changes in the urinary tract [14,15] and to severe incontinence being more common in older than younger patients with OAB [2,16] . Incontinence is more prevalent in women [17,18] and our population was predominantly female, although 55% of men also presented with wet OAB.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of stent-related symptoms has not been clearly proved yet, pain and LUTS caused by stent placement have been attributed to the pressure transmitted to the renal pelvis during urination, bladder ischemia and lower ureteric and bladder spasm due to local irritation [6][7][8] . The stent-related symptoms resemble LUTS secondary to benign prostatic hyperplasia (BPH) and overactive bladder (OAB) symptoms caused by urethral and bladder resistance, bladder instability and involuntary bladder contraction [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Though pain and lower urinary tract symptoms (LUTS) caused by stent placement have been attributed to the pressure transmitted to the renal pelvis during urination, bladder ischemia and lower ureteric and bladder spasm due to local irritation [6][7][8] , the exact pathophysiology of ureteral stent-related symptoms is not clear. For this reason, several attempts to alleviate ureteral stentrelated symptoms have been reported, such as improving stent materials, physical properties and design [9] .…”
mentioning
confidence: 99%
“…Azadzoi et al [16] also showed that ischemia and hypoxia might induce bladder neuropathy and lead to overactive bladder in the rabbit. Also, recent data supported that ischemia is associated with several physiological and pathological alteration in the bladder with OAB [17]. Although it is not proper to extrapolate these findings, alteration of blood flow at bilateral NVB vessels may reflect the different degree of hypoxia or congestion in the base of the bladder, since the inferior vesical artery provides blood to both branches along the prostate (NVB vessels) and the branches into the bladder neck and trigonal area [18].…”
Section: Discussionmentioning
confidence: 99%